Doc in the box. - JERRAM, Peter (1993)
Identifies the steps to be followed after deciding to distribute documents on-line, viz., (1) defining the nature of the information the system will handle, and choosing the system best suited to the documentation; (2) converting documents already in print; (3) look at the graphics; (4) develop and offer writer training.